VIP boosts regulatory T cell induction by trophoblast cells in an in vitro model of trophoblast–maternal leukocyte interaction - Fraccaroli, Laura Virginia (2015)
Inducible regulatory T cells (Tregs) exert a timely and efficient immunosuppressive action at the critical peri-implantation stage essential for maternal tolerance to the conceptus. Vasoactive intestinal peptide (VIP) promotes anti-inflammatory and tolerogenic profiles through binding to VIP receptors on immune cells. We evaluated whether VIP produced by trophoblast cells induces Tregs during the early interaction of maternal leukocytes with trophoblast cells, thus contributing to maternal tolerance. We used an in vitro model of maternal leukocyte–trophoblast cell interaction represented by cocultures of fertile women’s PBMCs with a human trophoblast cell line (Swan-71) and evaluated the effect of VIP added exogenously and of the endogenous polypeptide. VIP increased the frequency of CD4+CD25+FoxP3+ cells after coculture, and these cells were able to suppress the maternal alloresponse. VIP also increased the frequency of CD4+IL10+ and CD4+TGFβ+ cells, but it did not modulate IFN-γ or IL-17 production. Swan-71 secreted VIP, and their coculture with maternal PBMCs significantly increased the frequency of Tregs. This effect was even more pronounced if the trophoblast cells had been pretreated with VIP. In both situations, the VIP antagonist prevented the increase in the frequency of CD4+Foxp3+ cells, reflecting a specific effect of the polypeptide after the interaction with Swan-71 cells. Finally, the increase in CD4+CD25+FoxP3+ frequency was prevented by an anti–TGF-β Ab and a VIP antagonist. These results suggest that VIP could have an active role in the immunoregulatory processes operating in the maternal–placental interface by contributing to the induction of Tregs through a mechanism involving TGF-β1.